2001
DOI: 10.1590/s0102-79722001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Criando Falsas Memórias em Adultos por meio de Palavras Associadas

Abstract: Ao longo deste século, os pesquisadores têm se interessado pelos estudos da falsificação da memória, o fato de lembrarmos de eventos que na realidade não ocorreram, e de como se dá esse processo. As falsas memórias referem-se a uma gama de fenômenos que têm sido observados tanto em pesquisas experimentais, quanto no âmbito da psicoterapia, na área jurídica, bem como em outras variadas situações do cotidiano. As questões relacionadas à habilidade de crianças e adultos em relatar fidedignamente os fatos vividos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
26

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
0
8
0
26
Order By: Relevance
“…Some of these studies have used the Deese-Roediger-McDermott paradigm (DRM; Roediger & McDermott, 1995), which was adapted to the Brazilian population (Stein & Perguer, 2001;Stein, Feix, & Rohenkohl, 2006), and was design to examine whether emotional critical lures could be falsely remembered (Budson et al, 2006;Kensinger & Corkin, 2004a;Pesta, Murphy, & Sanders, 2001). The DRM paradigm involves the presentation of lists of words (e.g., table, sit, legs, seat…), each of which is highly associated with a single, non-presented word (e.g., chair), referred to as the critical lure.…”
Section: Emotion and Memory Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies have used the Deese-Roediger-McDermott paradigm (DRM; Roediger & McDermott, 1995), which was adapted to the Brazilian population (Stein & Perguer, 2001;Stein, Feix, & Rohenkohl, 2006), and was design to examine whether emotional critical lures could be falsely remembered (Budson et al, 2006;Kensinger & Corkin, 2004a;Pesta, Murphy, & Sanders, 2001). The DRM paradigm involves the presentation of lists of words (e.g., table, sit, legs, seat…), each of which is highly associated with a single, non-presented word (e.g., chair), referred to as the critical lure.…”
Section: Emotion and Memory Accuracymentioning
confidence: 99%
“…These authors interpreted this finding as evidence for the proposal that when items produce high levels of interference, as in the case of the DRM critical distracters, cognitive control processes supported by the left dorsolateral PFC are responsible for the maintenance of accuracy (i.e., they prevent false recognition). Sene, Lopes and Rossini (2014), using the Brazilian version of the DRM lists (Stein & Perguer & 2001;Stein et. al, 2006), showed that RTs were significantly increased as a function of test type due to an increase in memory load, and this increase was higher for critical distracters (FMs) with a memorized set of seven words.…”
Section: False Memories In Short-term Tasks: Contributions Of Reactiomentioning
confidence: 99%
“…Na fase de teste da memória, os participantes realizam um teste de recordação ou de reconhecimento com a presença do distrator crítico (nome dado à palavra crítica quando apresentada no teste de reconhecimento). O uso do procedimento DRM tem produzido altos índices de falsas recordações e falsos reconhecimentos (Karpicke, McCabe & Roediger, 2008;Roediger, McDermott, Pisoni & Gallo, 2004), caracterizados pela falsa lembrança da palavra crítica (e.g., Stein & Pergher, 2001). Além disso, também permite a obtenção de índices de memória verdadeira.…”
Section: O Paradigma Deese-roediger-mcdermott (Drm)unclassified
“…Word association norms are used to create tasks to evaluate memory and language processes (e.g., false memory; Roedinger & McDermott, 1995;Stein, Feix, & Rohenkohl, 2006) in clinical neuropsychiatry (Bhatt, Laws, & McKenna, 2010) and non-clinical samples (Stein & Pergher, 2001). Due to changes over time in the cultural and linguistic meaning and use of words (Hirsh & Tree, 2001), continuously updating such norms is important.…”
Section: Introductionmentioning
confidence: 99%